EFEKTIVITAS PENANGANAN KAWASAN PEMUKIMAN KUMUH DI KOTA MAKASSAR - Lahya, Raudatul Jannah; Mappamiring, Mappamiring; Harakan, Ahmad (Universitas Muhammadiyah Makassar, 2024)
This study aims to determine the effectiveness of handling slum areas in Maccini Sombala Village, Tamalate District, Makassar City. In this study, qualitative methods were used to obtain data (primary data and secondary data) through data collection techniques in the form of observation and interviews with relevant informants. The results of this study indicate that the effectiveness of handling slum areas is not running effectively based on 1) Achievement of the objectives to be achieved by the Housing and Settlement Area Office of Makassar City and Maccini Sombala Village to reduce slum settlements, by providing assistance in the form of groceries and building materials to the community , Has been running effectively 2) Integration carried out by the Housing and Settlement Area Office of Makassar City and Maccini Sombala Village in the form of socialization regarding waste and environmental hygiene, but in reality there was not a single socialization carried out. So you can say it's not effective. 3) Adaptation carried out by the Housing and Settlement Area Office of Makassar City, Maccini Sombala Village, by visiting or checking the location directly to the community as well as seeing the condition of the people living in slum settlements.